Race riots : comedy and ethnicity in modern British fiction - Ross, Michael L., 1936- (McGill-Queen's University Press, 2006)
Ross examines racial humour as a manifestation of post-colonialism and questions contemporary critiques of "political correctness." Looking at cartoons from pre-World War II issues of Punch, Ross shows how disdain for non-Europeans plays a key role in period British humour and links this idea to the racial humour in the work of Evelyn Waugh and Joyce Cary. He also demonstrates how these assumptions are later turned on their heads by writers such as Salman Rushdie.